أثر استخدام الأفلام التربوية لتنمية مهارة الاستماع في قسم تعليم اللغة العربية بجامعة أنتساري الإسلامية الحكومية بنجرماسين - Kamil Rama Ounsyar, Muhammad (UIN ANTASARI, 2021)
This research is aimed to find out significant effect of using Animation movie to improve students’ listening skill at Antasari State Islamic University in academic 2019/2020. The design of this research was quasi experimental by using pre-test and post-test. Population and sample of the research is the students’ fifth semester Arabic Education Study Program. The number of sample is selected by using cluster random sampling technique and then analyzed the data by using independent sample T-test. After analyzing the data, the researcher found out there was a significant effect by using Animation Movie to improve students’ listening skill. Where T-table showed 2.4, at significance level of 5%, it showed 2.00 and at level of 1%, it showed 266. Thus, null hypothesis (Ho) was rejected, and alternative hypothesis (Ha) was accepted which showed 2.06 < 2.4 > 2.79. In conclusion, there was a significant effect of using Animation Movie to Improve Students’ Listening Skill at Arabic language education